Brief Report: Differences in Types of Myocardial Infarctions Among People Aging With HIV. (1st February 2021) - Crane, Heidi M.; Nance, Robin M.; Whitney, Bridget M.; Heckbert, Susan R.; Budoff, Matthew; High, Kevin; Landay, Alan; Feinstein, Matthew; Moore, Richard D.; Mathews, William Christopher; Christopoulos, Katerina; Saag, Michael S.; et al.
Abstract : Background: Type 1 myocardial infarctions (T1MIs) result from atherosclerotic plaque instability, rupture, and/or erosion. Type 2 MIs (T2MIs) are secondary to causes such as sepsis and cocaine-induced vasospasm resulting in an oxygen demand–supply mismatch and are associated with higher mortality than T1MIs. T2MIs account for a higher proportion of MIs among people living with HIV (PLWH) compared with the general population. We compared MI rates by type among aging PLWH. We hypothesized that increases in MI rates with older age would differ by MI types, and T2MIs would be more common than T1MIs in younger individuals. Methods: Potential MIs from 6 sites were centrally adjudicated using physician notes, electrocardiograms, procedure results, and laboratory results. Reviewers categorized MIs by type and identified causes of T2MIs. We calculated T1MI and T2MI incidence rates. Incidence rate ratios were calculated for T2MI vs. T1MI rates per decade of age. Results: We included 462 T1MIs (52%) and 413 T2MIs (48%). T1MI rates increased with older age, although T1MIs occurred in all age decades including young adults. T2MI rates were significantly higher than T1MI rates for PLWH younger than 40 years. T1MI rates were similar or higher than T2MI rates among those older than 40 years (significantly higher for those aged 50–59 and 60–69 years). Conclusions: Rates of T2MIs were higher than T1MIs until age 40 years among PLWH, differing from the general population, but rates of both were high among older PLWH. Given prognostic differences between MI types, these results highlight the importance of differentiating MI types among PLWH. Abstract : Supplemental Digital Content is Available in the Text.